Development of an ONT for NG-PON2 - Rodrigues, Cláudia Gonçalves (2019)
The constant emergence of new products and services through communication networks, namely the Internet, leads to the demand for technology capable of providing these services with increasing speeds and bandwidth. Nowadays, the technology suitable to provide these features is communication through an optical fiber (optical communications). This technology is applied by PON networks, in which architectures distribute optical fiber from the central office (OLT) through the final user (ONT or ONU). It is in the context of these networks that arise the integrated optical applications for implementation of these structures (OLTs and ONTs) for data transmission and reception with reduced energy consumption, complexity as well as size. Therefore, these chips pretend to include, in one single copy, several optical components multiplying its functionalities in very reduced sizes and, for power consume reduction, using mostly passive elements. This dissertation intends to contribute with new solutions development for implementation of new structures capable to meet the user needs, with a development of a new architecture for implementing a PIC transmitter to be integrated on the client-side at the ONT. The optoelectronic solution should be capable of address 40 GBit/s of data rate and, for that, it should also be evaluated an implementation method to apply channel multiplexing to the system that, at the same time that it allows the 40 Gbit/s bit rate output, presents low additional loss values to the system. The proposal architecture should also ensure an 8 dBm of minimum output optical power. Besides, the final chip must be compliant with NG-PON2 network requirements